Flow injection chemiluminescence determination of 2‐methoxyestradiol based on inhibition of luminol‐potassium ferricyanide reaction. (20th April 2012) - Jin, Jianwen; Yao, Hanchun; Chen, Zheng; Pang, Li; Du, Bin
ABSTRACT: A novel flow‐injection chemiluminescence (FI‐CL) method is described for the determination of 2‐methoxyestradiol (2‐ME). The method is based on the inhibitory effect of 2‐ME on the CL reaction of luminol and potassium ferricyanide in alkaline solution. Under optimal conditions, net CL intensity was proportional to 2‐ME concentration in synthetic and mouse plasma samples. Corresponding linear regression equations were 8.0 x 10 ‐9 ‐1.0 x 10 ‐7 g/mL for synthetic samples and 2.0 x 10 ‐9 ‐1.0 x 10 ‐7 g/mL for plasma samples. Detection limit for synthetic samples and limits for quantification of plasma samples were 8.4 x 10 ‐10 g/mL (3σ) for synthetic samples and 4.0 x 10 ‐9 g/mL for mouse samples. A complete analysis was performed for 60 s, including washing and sampling, resulting in a throughput of ≈ 60/h. The proposed method was applied for the determination of 2‐ME in synthetic and mouse plasma samples. Percentage recoveries were 101.0‐102.8% and 98.0‐105.0%, respectively. A possible mechanism responsible for CL reaction is proposed. Copyright © 2012 John Wiley & Sons, Ltd.